2004
DOI: 10.1002/aic.10154
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of monochlorobiphenyl isomers in supercritical water in the presence of methanol

Abstract: Comprehensive studies of monochlorobiphenyl (MCB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Anitescu et al carried out a comprehensive study on the decomposition of tetrachlorobiphenyl and monochlorobiphenyl in the presence of methanol to understand the reaction kinetics and co-oxidative relationship between the reactive and stable species. , It is suggested that the dichlorination reaction dominated over the SCWO of PCBs, but the oxygen molecule could not directly participate in it. In the presence of methanol, the oxygen molecule reacted with methanol to form free radicals at first, as written in .…”
Section: Supercritical Water Oxidation Processmentioning
confidence: 99%
“…Anitescu et al carried out a comprehensive study on the decomposition of tetrachlorobiphenyl and monochlorobiphenyl in the presence of methanol to understand the reaction kinetics and co-oxidative relationship between the reactive and stable species. , It is suggested that the dichlorination reaction dominated over the SCWO of PCBs, but the oxygen molecule could not directly participate in it. In the presence of methanol, the oxygen molecule reacted with methanol to form free radicals at first, as written in .…”
Section: Supercritical Water Oxidation Processmentioning
confidence: 99%
“…The reaction system with no inter-phase mass-transfer limitations leads to a fast reaction rate and high oxidation efficiency. Previous studies have achieved the degradation of chlorinated hydrocarbons including PCBs by the O 2 -SCWO processes (with or without cosolvent) in the temperature range of 420-500 • C [3][4][5]. Another study has carried out the SCWO of PCBs using hydrogen peroxide (H 2 O 2 ) as an oxidant at 400 • C [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Kinetic studies of organic mixtures have attracted attention for treating practical wastes usually containing complex chemical mixtures, as well as studies on the co-oxidation of simple mixtures in supercritical water (see Table S1 in the Supporting Information). Most reports, including one recently from our group on the co-oxidation of alcohol with a compound, have shown that alcohol enhances conversion of the coexisting recalcitrant compound at 530 °C.…”
Section: Introductionmentioning
confidence: 99%